TRANSFORMING HEALTHCARE GOVERNANCE THROUGH LOCAL WISDOM: JENGAH NGAYAH-BASED TRADITIONAL HEALTH TOURISM MODEL AT TAMAN USADA BALI - Nandaka, I Ketut Tirka; Semara, I Made Trisna; Yadnya, Ida Bagus Putra; Saputra, I Putu David Adi (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
The commodification of Balinese culture in tourism and the systemic dysfunction of modern, mechanistic healthcare governance highlight a critical need for holistic healing alternatives. Although traditional health tourism (Usada) in Desa Baru, Tabanan Regency, offers significant potential as an antithesis to this issue, its management remains sub-optimal. This study aims to analyze the existing governance dynamics and design a health tourism governance model rooted in local wisdom. Employing a qualitative approach with a multi-site case study design, data were collected through participatory observation and in-depth interviews with key informants, followed by thematic analysis. The findings reveal that addressing the failure of modern medical institutions to provide equitable and empathetic care requires a fundamental paradigm shift. Consequently, this study formulates the "Integrated Governance Model Based on Jengah Ngayah," which adapts the autonomous structure of the Desa Adat (customary village) and synthesizes it with the philosophies of Tri Hita Karana, Taru Pramana, and Bayu Pramana. The novelty of this research lies in redefining the service paradigm from transactional medical interventions to yadnya (spiritual devotion), creating a unique hybrid of community-based governance and traditional healing. In conclusion, this model effectively fosters a non-discriminatory, comprehensive healing environment. The practical implications suggest that integrating indigenous spiritual values into tourism governance not only secures a competitive destination advantage but also preserves local cultural authenticity through sustainable holistic healing experiences.